Animal Models, Learning Lessons to Prevent and Treat Neonatal Chronic Lung Disease - Jobe, Alan H. (Frontiers in Medicine, 2015)
Chronic lung disease (bronchopulmonary dysplasia – BPD) is a consequence of the integrated effects of antenatal exposures, very preterm birth, and postnatal interventions that injure the very immature lung at the saccular stage of lung development. Results with animal models have established that excessive oxygen, trauma from stretch of the airspaces and infection are the major variables that injure the immature lung. Persistent inflammation seems to be the initial pathway contributing to injury initiation and persistence, which disrupts normal development programs and requires simultaneous repair programs to remodel the injured lung. Animal models focus primarily on the mechanisms of the early injury using preterm or term animals that are normal, while expression of the human disease is likely preconditioned by fetal and early neonatal exposures. A surprising number of interventions to block inflammatory cell recruitment or function, inhibit cytokine actions, augment nitric oxide, or increase anti-oxidants for example, can prevent much of the pathophysiology of BPD in animal models. However, these treatments either have modest or no benefits or have not been tested in humans. Potential off target effects of therapies on lung development and injury repair make translation of results from animal models to preterm infants a challenge. Animal models have provided essential insights into the pathophysiology of BPD and and will be essential for development and testing of new therapies.